Efficient biosynthesis of exopolysaccharide in Candida glabrata by a fed-batch culture - Xu, Sha; Xu, Jinke; Zeng, Weizhu; Shan, Xiaoyu; Zhou, Jingwen (Frontiers in Bioengineering and Biotechnology, 2022)
Polysaccharides are important natural biomacromolecules. In particular, microbial exopolysaccharides have received much attention. They are produced by a variety of microorganisms, and they are widely used in the food, pharmaceutical, and chemical industries. The Candida glabrata mutant 4-C10, which has the capacity to produce exopolysaccharide, was previously obtained by random mutagenesis. In this study we aimed to further enhance exopolysaccharide production by systemic fermentation optimization. By single factor optimization and orthogonal design optimization in shaking flasks, an optimal fermentation medium composition was obtained. By optimizing agitation speed, aeration rate, and fed-batch fermentation mode, 118.6 g L−1 of exopolysaccharide was obtained by a constant rate feeding fermentation mode, with a glucose yield of 0.62 g g−1 and a productivity of 1.24 g L−1 h−1. Scaling up the established fermentation mode to a 15-L fermenter led to an exopolysaccharide yield of 113.8 g L−1, with a glucose yield of 0.60 g g−1 and a productivity of 1.29 g L−1 h−1.